Cerebral radiofrequency exposures during adolescence: Impact on astrocytes and brain functions in healthy and pathologic rat models. Issue 5 (7th June 2016) - Petitdant, Nicolas; Lecomte, Anthony; Robidel, Franck; Gamez, Christelle; Blazy, Kelly; Villégier, Anne‐Sophie
Abstract : The widespread use of mobile phones by adolescents raises concerns about possible health effects of radiofrequency electromagnetic fields (RF EMF 900 MHz) on the immature brain. Neuro‐development is a period of particular sensitivity to repeated environmental challenges such as pro‐inflammatory insults. Here, we used rats to assess whether astrocyte reactivity, perception, and emotionality were affected by RF EMF exposures during adolescence. We also investigated if adolescent brains were more sensitive to RF EMF exposures after neurodevelopmental inflammation. To do so, we either performed 80 μg/kg intra‐peritoneal injections of lipopolysaccharides during gestation or 1.25 μg/h intra‐cerebro‐ventricular infusions during adolescence. From postnatal day (P)32 to 62, rats were subjected to 45 min RF EMF exposures to the brain (specific absorption rates: 0, 1.5, or 6 W/kg, 5 days/week). From P56, they were tested for perception of novelty, anxiety‐like behaviors, and emotional memory. To assess astrocytic reactivity, Glial Fibrillary Acidic Protein was measured at P64. Our results did not show any neurobiological impairment in healthy and vulnerable RF EMF‐exposed rats compared to their sham‐exposed controls. These data did not support the hypothesis of a specific cerebral sensitivity to RF EMF of adolescents, even after a neurodevelopmental inflammation. Bioelectromagnetics. 37:338–350, 2016. © 2016 Wiley Periodicals, Inc.